Application of the Weighted Product Method in Determining the Selection of Exemplary Students at Public Junior High School 67 Central Maluku - Yulyana Berhitu; Dorteus L. Rahakbauw; Venn Yan Ishak Ilwaru (Pattimura International Journal of Mathematics (PIJMath), 2024)
To consider student learning outcomes each semester, the school usually selects exemplary students each year. It is done so that the enthusiasm for learning continues to increase. It is hoped that the selection of exemplary students can be a benchmark for students so that they continue to develop and deepen the knowledge they are learning. Some of the problems that occur in every school, especially at Public Junior High School 67 Central Maluku, in determining exemplary students are less effective and still require a lot of time to process and know the results of determining exemplary students. Based on the analysis that had been done, researchers used the Weighted Product method in processing data to produce exemplary students, which aimed to reduce the occurrence of errors in determining exemplary students and made it easier for schools to determine exemplary students. The Weighted Product method is one of the methods used to solve decision-making systems by considering criteria and weights. From the results of calculations using the Weighted Product method and manual calculations, it was found that Yunita D Firnanda was ranked first with the results of calculations using the Weighted Product method of 0.0149912 and manual calculations of 964, for the second rank using the Weighted Product method of 0.014292153 and manual calculations of 957 on behalf of Jordi Parinussa and the third rank on behalf of Sri Meilans Kinyari with the results of calculations using the Weighted Product method of 0.014146707 and manual calculations of 946.